Voriconazole as therapy for systemic Penicillium marneffei infections in AIDS patients - Khuanchai Supparatpinyo (2018)
The objective of this study was to evaluate the triazole anti-fungal agent, voriconazole, as therapy for systemic Penicillium marneffei infections in patients with advanced HIV infection. Patients with systemic P. marneffei infection were enrolled into a study of voriconazole for the treatment of less common, emerging, or refractory fungal infections. Patients were eligible for inclusion in the study on the basis that no anti-fungal agents have received regulatory approval specifically for P. marneffei infections. Patients were treated in the hospital setting with intravenous voriconazole (6 mg/kg every 12 hours on Day 1 and then 4 mg/kg every 12 hours for at least 3 days, after which patients could switch to oral therapy at 200 mg twice a day) or as outpatients with oral voriconazole (400 mg twice a day on Day 1 and then 200 mg twice a day) for a maximum of 12 weeks. Eleven patients received treatment with voriconazole. Two received short courses of intravenous therapy followed by the oral formulation; nine were treated with oral voriconazole only. At the end of therapy, eight of the nine evaluable patients had favorable response to therapy, based on mycological and clinical findings. There were no relapses of P. marneffei infection in the six patients who were seen at follow-up within 4 weeks of the end of therapy. Treatment with voriconazole was well tolerated, with no discontinuations caused by drug-related adverse events. The results of this study suggest that voriconazole is an effective, well-tolerated, and convenient option for the treatment of systemic infections with P. marneffei. Copyright © 2007 by The American Society of Tropical Medicine and Hygiene.